Governing Habits Treating Alcoholism in the Post-Soviet Clinic - Raikhel, Eugene (Expertise: Cultures and Technologies of Knowledge, 2016)
Critics of narcology-as addiction medicine is called in Russia-decry it as being "backward," hopelessly behind contemporary global medical practices in relation to addiction and substance abuse, and assume that its practitioners lack both professionalism and expertise. On the basis of his research in a range of clinical institutions managing substance abuse in St. Petersburg, Eugene Raikhel increasingly came to understand that these assumptions and critiques obscured more than they revealed. Governing Habits is an ethnography of extraordinary sensitivity and awareness that shows how therapeutic practice and expertise is expressed in the highly specific, yet rapidly transforming milieu of hospitals, clinics, and rehabilitation centers in post Soviet Russia. Rather than interpreting narcology as a Soviet survival or a local clinical world on the wane in the face of globalizing evidence-based medicine, Raikhel examines the transformation of the medical management of alcoholism in Russia over the past twenty years. Raikhel's book is more than a story about the treatment of alcoholism. It is also a gripping analysis of the many cultural, institutional, political, and social transformations taking place in the postSoviet world, particularly in Putin's Russia. Governing Habits will appeal to a wide range of readers, from medical anthropologists, clinicians, to scholars of post-Soviet Russia, to students of institutions and organizational change, to those interested in therapies and treatments of substance abuse, addiction, and alcoholism.